Ecclesial Belonging in a World of Pure Experience: William James, W. E. B. Du Bois, and Religious Rationality in Crisis - Stepanenko, Walter Scott (Open theology, 2021)
The global COVID-19 pandemic has spotlighted several instances of churches violating state issued and scientifically recommended guidelines designed to keep populations healthy and to prevent the further spread of the disease. While these instances are minority responses to these orders, they nonetheless raise questions about the rationality of ecclesial belonging in response to the COVID-19 pandemic. In this article, I draw on the work of William James and W. E. B. Du Bois to articulate a conception of ecclesial belonging as a social epistemological process engaging a complex, fluid multiplicity of knowers of various scales. I argue that, in this view, ecclesial rationality involves the construction of a concatenation of internal and external practices individual believers and groups can traverse so long as they consistently satisfy a plurality of desiderata. I suggest that what is irrational about religious-based defiance of COVID-19 guidelines is the church-sanctioned severance of internal from external practices. I suggest that this behavior is supported by a failure to grasp the demands of ecclesial rationality rather than embrace them, and that this conception of rationality may have been eroded by the value-neutral skepticism of secular rationality.